Arthroscopic Repair of Posterior Cruciate Ligament Tibial Avulsion Fractures Using a “Y”-Shaped Suture Technique Combined With Suspension Fixation - Zijiang Yang, M.Med.; Tao He, M.Med.; Huai Shao, M.Med.; Ming Zou, M.Med.; Min Yu, M.D. (Arthroscopy Techniques)
The posterior cruciate ligament (PCL) plays a crucial role for the posterior stability of the knee joint, accounting for 3% to 38% of acute knee injuries and frequently co-occurring with other ligament injuries. PCL tibial avulsion fractures are not rare in clinical practice. Arthroscopic treatment for PCL tibial avulsion fractures has gained acceptance due to its ability to achieve anatomic reduction, restore ligament tension, and improve joint stability while minimizing surgical trauma and facilitating rapid recovery. However, the choice of fixation method remains a topic of ongoing debate. We employed a “Y”-shaped suture technique combined with suspension fixation in the arthroscopic treatment of PCL tibial avulsion fractures. This technique effectively stabilizes the fracture while restoring PCL tension, resulting in improved recovery of knee stability and function.